ANALISIS KOMPENSASI DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA PT KANSAI INDO WARNA - Mauli Siagian,; Falentino, (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2019)
This study aims to determine the effect of compensation and motivation on employee performance. This research was conducted at PT Kansai Indo Warna. The population in this study amounted to 115 people. In this study the sampling technique used as a simple random sampling technique with 115 respondents. This analysis uses multiple regression analysis using SPSS (Statistical Product and Service Solution) version 23. This study produces multiple linear regression equations and has an R Square (R2) value in this study of 46.3% . Based on the results of the partial t-test research the results show that compensation has a positive and significant effect on employee performance. Motivation has a positive and significant effect on employee performace. Based on the results  of  the F test, the results showed that compensation and motivation together had a positive and significant effect on employee performance at PT Kansai Indo Warna